PENGARUH VARIASI LAJU VOLUME AIR PENDINGIN DI KONDENSOR TERHADAP PERFORMANSI PROSES PIROLISIS PLASTIK LOW DENSITY POLYTHYLENE (LDPE) - Mahardika, Fahmi; Suarnadwipa, I Nengah; Murti, Made Ricki (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract The waste problem remains unresolved, with waste production increasing due to population growth, consumption patterns, and lifestyles; organic waste accounts for 60-70%, while plastic waste is 14%, especially plastic bags. Pyrolysis methods that are environmentally friendly and do not produce harmful gases such as COx, NOx, SOx are used to convert plastics into fuel oil with certain characteristics, where the condenser plays an important role in determining the oil yield with the condenser water flow method giving more results than other methods, so research is needed to vary the cooling water rate in the condenser for optimal pyrolysis results. The purpose of this study was to determine the effect of varying the volume rate of cooling water in the condenser on oil volume, cooling capacity, and pyrolysis process yield ratio. This research uses LDPE plastic waste that has been cut with a size of 1 cm × 1 cm then in the pyrolysis process varies the cooling water rate with a value of 0.08 L/min, 2 L/min, 6.1 L/min, 7 L/min, and 7.8 L/min. The results obtained in this study are the higher the cooling water flow rate in the condenser, the more oil produced in the pyrolysis process in this study as much as 535 mL and there is an increase in the ratio of oil to LDPE plastic used as much as 41.463%. However, in this study, the higher the cooling water flow rate in the condenser, there will be a decrease in the cooling capacity of the condenser with the lowest value of 43.6559 Watt. Keywords: Pyrolysis, LDPE Plastic, Condenser, Cooling Water Rate, Cooling Capacity